2016
DOI: 10.1016/j.neulet.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Novel environment influences the effect of paradoxical sleep deprivation upon brain and peripheral cytokine gene expression

Abstract: Sleep loss increases inflammatory mediators in brain and peripheral tissues, but the mechanisms underlying this association are not fully understood. Male C57BL/6j mice were exposed to paradoxical sleep deprivation (PSD) for 24 h using the modified multiple platform (MMP) technique (platforms over water) or two different controls: home cage or a dry platform cage, which constituted a novel environment. PSD mice exhibited increased IL-1β and TNF-α pro-inflammatory gene expression in brain (hypothalamus, hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…In agreement with the present findings, a recent study demonstrated an elevated corticosterone concentration in the serum of PSD rats when compared to controls . In addition, and corroborating the findings of the present study, several studies have demonstrated that the levels of corticosterone are increased after PSD . Suchecki and colleagues showed that PSD induced using different methods increased ACTH and corticosterone secretion.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the present findings, a recent study demonstrated an elevated corticosterone concentration in the serum of PSD rats when compared to controls . In addition, and corroborating the findings of the present study, several studies have demonstrated that the levels of corticosterone are increased after PSD . Suchecki and colleagues showed that PSD induced using different methods increased ACTH and corticosterone secretion.…”
Section: Discussionsupporting
confidence: 93%
“…Although pro-inflammatory cytokines, such as IL-1 and TNF, are typically associated with development of an inflammatory response (Ashley et al, 2012; Medzhitov, 2008), there is increasing evidence that these cytokines play a role in mediating physiological and behavioral processes in healthy animals. For example, cytokine secretion is tied to biological rhythms and the sleep/wake cycle (Opp, 2005), and experimental sleep loss leads to the induction of a pro-inflammatory response in brain and peripheral tissues (Ashley et al, 2016; Dumaine and Ashley, 2015; Faraut et al, 2012). Whether such an inflammatory response is adaptive (at the least in the short term) remains to be seen.…”
Section: Nei Circuits and Behaviormentioning
confidence: 99%
“…We have previously reported marked sleep fragmentation after administration of the same chemo regimen used in the present study10. As sleep disruption elicits an inflammatory response2627, this may have contributed to the enhanced splenic inflammation observed in animals injected at ZT 2. Additionally, glucocorticoid concentrations peak during the early active phase in nocturnal rodents28, and they are negative regulators of inflammation, acting through multiple mechanisms2930.…”
Section: Discussionmentioning
confidence: 50%